High Frequency of Haplotype HLA-DQ7 in Celiac Disease Patients from South Italy: Retrospective Evaluation of 5,535 Subjects at Risk of Celiac Disease - Tinto, Nadia; Cola, Arturo; Piscopo, Chiara; Capuano, Marina; Galatola, Martina; Greco, Luigi; Sacchetti, Lucia (PloS one, 2015)
Celiac disease (CD) has a strong genetic component mainly due to HLA DQ2/DQ8 encoding genes. However, a minority of CD patients are DQ2/DQ8-negative. To address this issue, we retrospectively characterized HLA haplotypes in 5,535 subjects at risk of CD (either relatives of CD patients or subjects with CD-like symptoms) referred to our center during a 10-year period. We identified loci DQA1/DQB1/DRB1 by sequence-specific oligonucleotide-PCR and sequence-specific primer-PCR; anti-transglutaminase IgA/IgG and anti-endomysium IgA by ELISA and indirect immunofluorescence, respectively. We diagnosed CD in 666/5,535 individuals, 4.2% of whom were DQ2/DQ8-negative. Interestingly, DQ7 was one of the most abundant haplotypes in all CD patients and significantly more frequent in DQ2/DQ8-negative (38%) than in DQ2/DQ8-positive CD patients (24%) (p<0.05). Our data lend support to the concept that DQ7 represents an additive or independent CD risk haplotype with respect to DQ2/DQ8 haplotypes but this finding should be verified in other large CD populations.